Positive electrode material, secondary battery, and electric device

By using lithium manganese iron oxide positive electrode material and controlling its distribution of iron manganese iron element ratio, combined with the outer surface cladding layer, the problem of poor circulation stability of the positive electrode material of the secondary battery is solved, and the cycle life of the secondary battery is significantly improved.

CN119695146APending Publication Date: 2025-03-25SUNWODA MOBILITY ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411850811.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The circulation stability of the existing secondary battery positive electrode materials is poor, resulting in a decrease in the fast charging cycle life.

Method used

Lithium manganese manganese oxide is used as the positive electrode material, and the expected value and variance of the normal distribution curve of the ratio of manganese manganese are ensured to show an inhomogeneous distribution. Meanwhile, the cladding layer disposed on the outer surface of the positive electrode material includes a carbon-based material, a metal oxide or an ionic conductor.

Benefits of technology

Effectively promote the conversion of the metastable phase into a stable crystal structure, avoid Mn dissolution and separation of Mn and Fe elements, and improve the reactivity of the positive electrode material and the cycle life of the secondary battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005190621710000181
    Figure BDA0005190621710000181
  • Figure BDA0005190621710000191
    Figure BDA0005190621710000191
  • Figure BDA0005190621710000201
    Figure BDA0005190621710000201
Patent Text Reader

Abstract

The invention discloses a positive electrode material, a secondary battery and an electric device, and belongs to the technical field of batteries. The positive electrode material provided by the invention shows non-uniform distribution of manganese and iron elements, can promote the metastable phase to be converted into a more stable crystal structure, avoids Mn dissolution in the cycle process, and effectively prolongs the cycle life of the battery. And the particle size distribution of the positive electrode material is non-uniform, and the positive electrode compaction density and the reaction activity specific surface can be effectively improved by matching the large and small particle sizes, so that the capacity and the charge-discharge speed are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a positive electrode material, a secondary battery and an electrical device. Background Art

[0002] The positive electrode material of secondary batteries is a key factor in determining their performance. 4 ) has a low theoretical capacity and poor conductivity, which affects the fast charging cycle life of secondary batteries. Therefore, the development of positive electrode materials with higher cycle performance has become a technical problem that needs to be solved urgently.

[0003] In recent years, researchers have replaced part of the iron element in lithium iron phosphate with manganese to obtain lithium iron manganese phosphate positive electrode, which effectively increased the charge and discharge platform voltage (3.4V to 4.1V), making the lithium iron manganese phosphate positive electrode material a combination of the high safety and low cost of lithium iron phosphate materials and the high power of ternary materials. The revival of low-cost lithium iron phosphate positive electrode has driven the application research of lithium iron manganese phosphate materials, which is considered to have the potential to replace lithium iron phosphate positive electrode and become the next generation of large-scale application positive electrode materials, with broad market prospects.

[0004] In view of this, this application is filed. Summary of the invention

[0005] The purpose of the present application is to overcome the deficiencies of the prior art and provide a positive electrode material, a secondary battery and an electrical device, wherein the positive electrode material has excellent cycle stability.

[0006] To achieve the above-mentioned object, the first aspect of the present application provides a positive electrode material, including manganese iron lithium oxide;

[0007] The positive electrode material satisfies: 0.5≤μ, σ 2 ≥0.05;

[0008] Wherein, μ is the expected value of the normal distribution curve of the manganese-iron element ratio in the positive electrode material;

[0009] σ 2 is the variance of the normal distribution curve of the manganese-iron element ratio in the positive electrode material.

[0010] As an embodiment of the present application, the average manganese to iron element ratio of the positive electrode material is 0.25-4.

[0011] As an embodiment of the present application, the particle size distribution curve of the positive electrode material includes a first peak and a second peak; the first peak is located between 100 and 300 nm, and the second peak is located between 300 and 800 nm.

[0012] As an embodiment of the present application, the peak area of the first peak is S1, and the peak area of the second peak is S2, satisfying: 1 ≤ S1 / S2 ≤ 4.

[0013] As an embodiment of the present application, 0.5 ≤ S1 / (S1 + S2) ≤ 0.8.

[0014] As an embodiment of the present application, 0.2 ≤ S2 / (S1 + S2) ≤ 0.5.

[0015] As an embodiment of the present application, it further includes a coating layer disposed on the outer surface of the lithium manganese iron oxide, and the coating layer includes at least one of a carbon-based material, a metal oxide, and an ion conductor.

[0016] As an embodiment of the present application, it satisfies at least one of the following (1) to (5):

[0017] (1) The carbon-based material includes one or more of artificial graphite, natural graphite, soft carbon, and hard carbon;

[0018] (2) The metal oxide includes at least one of aluminum oxide, magnesium oxide, titanium dioxide, lanthanum oxide, zirconium dioxide, antimony trioxide, antimony pentoxide, vanadium trioxide, vanadium pentoxide, and zinc oxide;

[0019] (3) The ion conductor includes at least one of LLZO, LLTO, LATP, a sulfide solid electrolyte, and a polymer ion conductor;

[0020] (4) The thickness of the coating layer is 1 to 100 nm;

[0021] (5) The coating layer accounts for 0.5 to 5% of the total mass of the positive electrode material.

[0022] As an embodiment of the present application, the lithium manganese iron oxide includes a compound with the molecular formula Li x Mn y Fe 1-y M z PO 4 where 0.9 ≤ x ≤ 1.1, 0 < y < 1, 0 ≤ z ≤ 0.05, and M includes at least one of In, La, Zr, Ce, W, Al, Ti, Sr, Mg, Sb, V, Zn, and Cu.

[0023] The second aspect of the present application provides a secondary battery, including a positive electrode sheet, and the positive electrode sheet includes the positive electrode material described above.

[0024] The third aspect of the present application provides an electrical device, including the secondary battery described above.

[0025] The beneficial effect of the present application is that the manganese and iron elements in the positive electrode material described in the present application are non-uniformly distributed, which can promote the transformation of its metastable phase into a more stable crystal structure, avoid Mn dissolution during the cycle, and avoid the separation of Mn and Fe elements, thereby effectively avoiding the transformation of Mn and Fe into relatively aggregated two phases, effectively improving the reaction activity specific surface area of ​​the positive electrode material, and improving the cycle life of the secondary battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 It is the particle size distribution curve diagram of Example 1 and Comparative Example 1.

[0027] Figure 2 This is the distribution and variance of ferromanganese elements and the ferromanganese element ratio diagram of Example 1.

[0028] Figure 3 This is the distribution and variance of ferromanganese elements and the ferromanganese element ratio diagram of comparative example 1. DETAILED DESCRIPTION

[0029] In order to make the purpose, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.

[0030] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0031] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values ​​of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0032] The inventors of this application have found that the stability of the structure needs to be taken into consideration when designing the lithium manganese iron phosphate positive electrode. The dissolution of Mn caused by the metastable phase during the cycle process will cause a decrease in the cycle life. Due to the inconsistency of the dynamics of the Fe platform and the Mn platform during the charge and discharge process, the initially uniformly distributed Mn and Fe elements will gradually separate and transform into relatively aggregated two phases after long-term cycling, resulting in a decrease in the cycle life.

[0033] Therefore, based on the above problems, the embodiment of the present application provides a positive electrode material, including manganese iron lithium oxide;

[0034] The positive electrode material satisfies: 0.5≤μ, σ 2 ≥0.05;

[0035] Wherein, μ is the expected value of the normal distribution curve of the manganese-iron element ratio in the positive electrode material;

[0036] σ 2 is the variance of the normal distribution curve of the manganese-iron element ratio in the positive electrode material.

[0037] The inventors of the present application have found that when μ and σ in the normal distribution curve of the manganese-iron ratio in the positive electrode material are 2 When the value satisfies the above range, the manganese-iron elements in the positive electrode material are unevenly distributed. The uneven distribution of manganese-iron elements can promote the transformation of the metastable phase into a stable crystal structure, avoid Mn dissolution during the cycle, and avoid the separation of Mn and Fe elements, thereby effectively avoiding the transformation of Mn and Fe into relatively aggregated two phases, effectively improving the reaction activity specific surface of the positive electrode material, and improving the cycle life of the secondary battery.

[0038] Among them, the method for obtaining the normal distribution curve of the manganese-iron element ratio is: dividing the horizontal axis of the manganese-iron element distribution intensity curve diagram of the positive electrode material into n parts, calculating the manganese-iron element ratio of each divided point, and constructing a manganese-iron element ratio normal distribution curve for the values ​​of the manganese-iron element ratios of n points, where n is a positive integer ≥4.

[0039] When n=16, an exemplary example is given, the abscissa of the manganese-iron element distribution intensity curve of the positive electrode material is divided into 16 parts, the manganese-iron element ratio corresponding to the abscissa of each divided point is calculated, and the manganese-iron element ratio normal distribution curve is constructed for the values ​​of the manganese-iron element ratio of the 16 points, thereby obtaining μ (expected value) and σ 2 Value (variance).

[0040] Among them, the manganese-iron element distribution intensity curve diagram mentioned can be obtained by conventional technical means in the field. The following is an exemplary method for obtaining the manganese-iron element distribution intensity curve diagram: use the EDS energy spectrum of the EDS element distribution tester to scan and collect the Mn / Fe elements of the target positive electrode material to obtain the Mn / Fe element distribution diagram, and then use image processing software to convert it into an 8-bit grayscale value mode, and then use the contour graphics function to convert it into a manganese-iron element distribution intensity curve diagram.

[0041] Exemplarily, the image processing software may be Image J.

[0042] In one embodiment, 0.9≤μ≤2, for example, it can be 0.9, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2 or a range consisting of any two of these values.

[0043] In one embodiment, 1.1≤μ≤1.5.

[0044] In one embodiment, 0.05≤σ 2 ≤0.2, for example, it can be 0.05, 0.06, 0.08, 0.1, 0.12, 0.14, 0.15, 0.16, 0.18, 0.2 or a range consisting of any two of these values. When the σ in the normal distribution curve of the manganese-iron ratio in the positive electrode material is 2 When the value meets the above range, the manganese and iron elements in the positive electrode material present a non-uniform distribution state, which can promote the transformation of the metastable phase into a stable crystal structure, avoid Mn dissolution during the cycle, and avoid the separation of Mn and Fe elements, thereby effectively avoiding the transformation of Mn and Fe into relatively aggregated two phases, effectively improving the reaction activity specific surface of the positive electrode material, and improving the cycle life of the secondary battery.

[0045] In one embodiment, 0.1≤σ 2 ≤0.15. When the σ in the normal distribution curve of the manganese-iron ratio in the positive electrode material is 2 When the value satisfies the above range, the impedance can be further reduced and the cycle performance of the secondary battery can be improved.

[0046] In one embodiment, the average manganese-iron element ratio of the positive electrode material is 0.25-4, for example, it can be 0.25, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.2, 1.4, 1.5, 1.6, 1.8, 2, 2.1, 2.2, 2.4, 2.5, 2.6, 2.8, 3, 3.2, 3.4, 3.5, 3.6, 3.8, 4 or a range consisting of any two of the values. By controlling the average manganese-iron element ratio of the positive electrode material within this range, it is possible to further promote the conversion of the metastable phase into a stable crystal structure, avoid Mn dissolution during the cycle process, improve the structural stability of the positive electrode material, reduce the attenuation caused by volume expansion and contraction during the cycle process, improve the conductivity of the positive electrode material, avoid the destruction of the structure of the positive electrode material during the charge and discharge process, and effectively improve the cycle performance of the secondary battery.

[0047] In one embodiment, the average manganese to iron ratio of the positive electrode material is 1-2.

[0048] In one embodiment, the particle size distribution curve of the positive electrode material includes a first peak and a second peak; the first peak is located between 100 and 300 nm, for example, it can be 100 nm, 120 nm, 140 nm, 150 nm, 160 nm, 180 nm, 200 nm, 220 nm, 240 nm, 250 nm, 260 nm, 280 nm, 300 nm or a range consisting of any two of these values.

[0049] In one embodiment, the second peak is located between 300 and 800 nm, for example, it can be 300 nm, 320 nm, 350 nm, 380 nm, 400 nm, 420 nm, 450 nm, 480 nm, 500 nm, 520 nm, 550 nm, 580 nm, 600 nm, 620 nm, 650 nm, 680 nm, 700 nm, 720 nm, 750 nm, 780 nm, 800 nm or a range consisting of any two of these values.

[0050] Among them, the particle size distribution curve of the positive electrode material described in the present application contains at least two peaks, and the particle size distribution range of the positive electrode material is wide and uneven, which can reduce the porosity, increase the compaction density of the positive electrode sheet, and improve the stability of the positive electrode material during the sheeting process, and effectively improve the cycle performance of the secondary battery; at the same time, it is beneficial to increase the specific surface area of ​​the positive electrode material, increase the contact area with the conductive agent and the electrolyte, effectively improve the conductivity of the positive electrode sheet, increase the reaction activity specific surface of the positive electrode, improve the ohmic internal resistance (Rs) and the electrochemical transfer internal resistance (Rct), and the reduction of Rs and Rct can effectively increase the output power of the battery, and at the same time can broaden the current boundary of the fast charging process, effectively improving the cycle performance of the secondary battery.

[0051] In the present application, the particle size distribution curve is obtained by laser diffraction testing. The particle size distribution curve is based on the particle size as the horizontal axis and the percentage content as the vertical axis. After the corresponding points are drawn according to the percentage content of each particle size, the points of each particle size percentage content are connected to form a wavy and smooth frequency curve.

[0052] More specifically, the particle size distribution curve is obtained by referring to the particle size distribution laser diffraction method test of GB / T 19077-2016: weigh 0.1g to 0.13g of the positive electrode active material sample to be tested in a 50mL beaker, add 5g of anhydrous ethanol, put in a stirring bar of about 2.5mm and seal it with plastic wrap. After ultrasonic treatment for 5min, the sample is transferred to a magnetic stirrer and stirred at 500 rpm for more than 20min. Two samples are taken from each batch of products for testing. The Mastersizer2000E laser particle size analyzer of Malvern Instrument Co., Ltd. is used for testing to obtain the particle size distribution curve.

[0053] In one embodiment, the peak area of ​​the first peak is S1, and the peak area of ​​the second peak is S2, satisfying: 1≤S1 / S2≤4, for example, it can be 1, 1.5, 2, 2.5, 3, 3.5, 4 or a range consisting of any two of these values. By controlling the ratio of S1 / S2 within the above range, the particle pores of the positive electrode material are filled to the maximum extent, effectively improving the compaction density and gram capacity of the positive electrode material, and improving the wettability of the electrolyte to the secondary particles, which can effectively reduce interfacial side reactions, reduce gas production of secondary batteries, improve the diffusion path of lithium ions, and further improve the cycle performance of secondary batteries.

[0054] In one embodiment, 0.5≤S1 / (S1+S2)≤0.8, for example, it can be 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8 or a range consisting of any two values ​​therein. By controlling S1 / (S1+S2) within this range, the diffusion distance of lithium ions in the positive electrode material can be effectively reduced, the deintercalation speed of lithium ions can be improved, the contact area with the electrolyte can be increased, the electrochemical reactivity of the secondary battery can be improved, and thus the cycle performance of the secondary battery can be improved.

[0055] In one embodiment, 0.2≤S2 / (S1+S2)≤0.5, for example, it can be 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5 or a range consisting of any two of these values. By controlling S2 / (S1+S2) within this range, the compaction density of the positive electrode sheet can be further improved, the stability of the positive electrode material during the sheeting process can be improved, and the cycle performance of the secondary battery can be effectively improved.

[0056] In one embodiment, it further includes a coating layer disposed on the outer surface of the manganese iron lithium oxide, and the coating layer includes at least one of a carbon-based material, a metal oxide, and an ion conductor.

[0057] Among them, for carbon coating, a hydrothermal method is usually used, in which the obtained manganese iron lithium oxide and the carbon source are melted in water, stirred and then sintered, thereby achieving carbon coating of the positive electrode material.

[0058] In one embodiment, the carbon source includes at least one of sucrose, glucose, citric acid, polyethylene glycol, and soluble starch.

[0059] In one embodiment, the carbon source is added in an amount of 1% to 5% wt of the total mass of the positive electrode powder.

[0060] In one embodiment, the sintering temperature is 800-900°C, for example, it can be 800°C, 810°C, 820°C, 830°C, 840°C, 850°C, 860°C, 870°C, 880°C, 890°C, 900°C or a range consisting of any two of the values.

[0061] Metal oxide coating is usually carried out by vapor deposition (CVD), in which manganese iron lithium oxide is placed in a tube furnace, and the corresponding metal source gas is introduced with oxygen through a high-temperature process, so that the corresponding metal oxide is deposited and coated on the surface of the powder.

[0062] For ionic conductors, hydrothermal coating is adopted, in which manganese iron lithium oxide and coating precursor are mixed in water accompanied by hydrolysis condensation reaction, and then the corresponding ionic conductor coated manganese iron lithium oxide is obtained through subsequent high-temperature sintering and curing.

[0063] In one embodiment, the carbon-based material includes one or more of artificial graphite, natural graphite, soft carbon, and hard carbon.

[0064] In one embodiment, the metal oxide includes at least one of aluminum oxide, magnesium oxide, titanium dioxide, lanthanum oxide, zirconium dioxide, antimony trioxide, antimony pentoxide, vanadium trioxide, vanadium pentoxide, and zinc oxide.

[0065] In one embodiment, the ion conductor includes at least one of LLZO (lithium lanthanum zirconium oxide), LLTO (lithium lanthanum titanium oxide), LATP (lithium aluminum titanium phosphate), sulfide solid electrolyte, and polymer ion conductor.

[0066] In one embodiment, the sulfide solid electrolyte includes Li 6 PS 5 Cl, Li 6 PS 5 Br, Li 6 PS 5 I. Li 10 G 2 S 12 , Li 2 SP 2 S 5 、LiSiPSCl、Li 7 P 3 S 11 , Li 5.5 PS 4.5 C l1.5 , Li 10 SnP 2 S 12 At least one of .

[0067] In one embodiment, the polymeric ionic conductor includes at least one of PEO-based solid polymer and polycarbonate.

[0068] In one embodiment, the thickness of the coating layer is 1 to 100 nm, for example, it can be 1 nm, 2 nm, 5 nm, 6 nm, 8 nm, 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, 50 nm, 55 nm, 60 nm, 65 nm, 70 nm, 75 nm, 80 nm, 85 nm, 90 nm, 95 nm, 100 nm, or a range composed of any two of these values.

[0069] In one embodiment, the coating layer accounts for 0.5 to 5% of the total mass of the positive electrode material. For example, it can be 0.5%, 0.6%, 0.8%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, or a range composed of any two of these values.

[0070] In one embodiment, the lithium manganese iron oxide includes a compound with the molecular formula Li x Mn y Fe 1-y M z PO 4 where 0.9 ≤ x ≤ 1.1, 0 < y < 1, 0 ≤ z ≤ 0.05, and M includes at least one of In, La, Zr, Ce, W, Al, Ti, Sr, Mg, Sb, V, Zn, Cu, and Cr.

[0071] In one embodiment, the mentioned M element can be incorporated into the lithium manganese iron oxide by doping and / or surface coating.

[0072] One embodiment of the present application provides a method for preparing a positive electrode material, including the following steps:

[0073] (1) According to the stoichiometric ratio, add an iron source, a manganese source, a phosphorus source, a lithium source, and a dopant containing the M element into a battery powder mixer, and then mix with pure water as a solvent. During the mixing and stirring process, add a complexing agent to adjust the pH to 8 to 9.5, and adjust the addition amount of ammonia water through a flow meter to control the pH value of the mixed solution to 10.2 to 10.5, so as to achieve a continuous increase in pH from low to high during the entire mixing process. Finally, obtain the target mixed precipitate through the coprecipitation method;

[0074] (2) Calcinate the mixed precipitate in step (1) under an inert atmosphere to obtain a calcined powder, and the calcined powder is pulverized and sieved to remove iron to obtain the positive electrode material.

[0075] In one embodiment, the molar ratio of Li:Fe:P:M in the lithium source, iron source, phosphorus source and dopant containing M element in step (1) is (1.0-1.1):(0.4-1.0):1:(0-0.03), for example, 1:0.9:1, 1.05:0.95:1, 1.1:0.9:1, 1.1:0.95:1, 1.05:1:1 or 1.1:1:1 or a range consisting of any two of these values.

[0076] In one embodiment, the manganese source includes at least one of manganese carbonate, manganese acetate, manganese phosphate, manganous phosphate, manganese dioxide, manganous manganic oxide, manganous sulfate, manganous nitrate, manganous oxalate, manganese sulfate, manganous nitrate, and manganous acetate.

[0077] In one embodiment, the iron source includes at least one of ferric phosphate, ferric oxide, ferrous sulfate, ferrous sulfate, ferrous nitrate, ferrous chloride, ferric acetate, and ferrous acetate.

[0078] In one embodiment, the phosphorus source includes at least one of diammonium hydrogen phosphate, ammonium dihydrogen phosphate, lithium dihydrogen phosphate, iron phosphate, manganese phosphate, and manganous phosphate.

[0079] In one embodiment, the dopant containing the M element includes at least one of nitrate, sulfate, chloride and acetate containing the M element.

[0080] The M element includes at least one of In, La, Zr, Ce, W, Al, Ti, Sr, Mg, Sb, V, Zn, Cu, and Cr.

[0081] Furthermore, the complexing agent of the coprecipitation method in step 1 includes one or more of ammonia solution, citric acid, ethylenediaminetetraacetic acid, disodium ethylenediaminetetraacetate, tetrasodium ethylenediaminetetraacetate, sodium gluconate and sodium alginate. The pH value of the solution is adjusted to enable the complexing agent to exert better complexing ability.

[0082] In one embodiment, the molar ratio of the lithium source to the iron source and the manganese source, calculated as Li and Fe+Mn, is (1.0-1.05):1, and the carbon source accounts for 5-10wt% of the total amount of the lithium source, the calcined powder and the carbon source, for example, it can be 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt% or a range consisting of any two of these values.

[0083] In one embodiment, the mixing in step (1) is performed in a mixer, and a special pH value changing process is used for mixing and stirring. 2+ and Mn 2+The pH value of the solution is set to 8.1-8.4 using a complexing agent, and then the raw materials such as iron source, manganese source, phosphorus source, lithium source and dopant are mixed and stirred. 2+ The threshold of complete precipitation is Mn 2+ The precipitation has just begun, so the Fe content in the precursor is higher than that in Mn. In the subsequent stirring process, the amount of complexing agent introduced is regulated by the flow meter to adjust the pH value, so that the pH value rises in stages during the entire mixing process until the pH value reaches the range of 10.2-10.5. At this time, Mn 2+ It also reaches the threshold of complete precipitation, so the proportion of Mn in the precursor gradually increases during the entire mixed precipitation process, and finally achieves an uneven distribution of the precursor Mn / Fe ratio.

[0084] In one embodiment, the addition flow rate of the ammonia solution is 1 to 5 L / h, for example, 1 L / h, 2 L / h, 3 L / h, 4 L / h, 5 L / h or a range consisting of any two values ​​therein.

[0085] In one embodiment, the concentration of the ammonia solution is 2-40%, for example, it can be 2%, 4%, 5%, 6%, 10%, 15%, 20%, 25%, 30%, 35%, 40 or a range consisting of any two of the values.

[0086] In one embodiment, the calcination temperature of step (2) is 500-800°C, for example, it can be 500°C, 520°C, 540°C, 550°C, 560°C, 580°C, 600°C, 620°C, 640°C, 650°C, 660°C, 680°C, 700°C, 720°C, 750°C, 780°C, 800°C or a range consisting of any two of the values.

[0087] In one embodiment, the step (2) adopts a two-step calcination, first calcining at 500-600°C for 1-4 hours, and then calcining at 700-800°C for 1-4 hours.

[0088] In one embodiment, the calcination time of step (2) is 1 to 4 hours, for example, 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours or a range consisting of any two values ​​therein.

[0089] An embodiment of the present application provides a secondary battery, including a positive electrode plate, wherein the positive electrode plate contains the positive electrode material described above.

[0090] More specifically, the positive electrode plate includes a positive electrode current collector and a positive electrode material layer disposed on at least one surface of the positive electrode current collector, and the positive electrode material layer includes the positive electrode material described above.

[0091] In the present application, the type of positive electrode current collector is not particularly limited, and it can be any known material suitable for use as a positive electrode current collector. In one embodiment, the positive electrode current collector includes metal materials such as aluminum, stainless steel, nickel plating, titanium, tantalum, and carbon materials such as carbon cloth and carbon paper.

[0092] There is no particular restriction on the form of the positive electrode current collector. When the positive electrode current collector is a metal material, the positive electrode current collector may be in the form of metal foil, metal cylinder, metal strip roll, metal plate, metal foil, metal plate mesh, stamped metal, foamed metal, etc. When the positive electrode current collector is a carbon material, the positive electrode current collector may include but is not limited to a carbon plate, a carbon film, a carbon cylinder, etc.

[0093] In one embodiment, the positive electrode material layer further includes a conductive agent and a binder.

[0094] In one embodiment, the secondary battery further includes a negative electrode plate, wherein the negative electrode plate includes a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode active material layer includes a negative electrode active material.

[0095] In the present application, there is no particular limitation on the negative electrode current collector, as long as the purpose of the present application can be achieved, for example, it can be copper foil, copper alloy foil, nickel foil, stainless steel foil, titanium foil, foam nickel, foam copper or a composite current collector.

[0096] In one embodiment, the negative electrode active material can be natural graphite, artificial graphite, mesophase microcarbon beads (MCMB), hard carbon, soft carbon, silicon, silicon-carbon composite, SiO, Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO 2 , spinel structure lithium titanate Li 4 Ti 5 O 12 , at least one of Li-Al alloy and metallic lithium.

[0097] In one embodiment, the negative electrode active material layer further includes a conductive agent and a binder.

[0098] In one embodiment, the type of the conductive agent mentioned in the present application is not limited, and any known conductive agent can be used.

[0099] In one embodiment, the conductive agent includes at least one of carbon materials such as acetylene black, needle coke, carbon nanotubes, and graphene.

[0100] In one embodiment, the type of binder mentioned in the present application is not limited, and any known positive electrode binder can be used.

[0101] In one embodiment, the binder includes at least one of polyethylene, polypropylene, polyethylene terephthalate, polymethyl methacrylate, polyimide, aromatic polyamide, cellulose, nitrocellulose, styrene-butadiene rubber, nitrile rubber, fluororubber, isoprene rubber, polybutadiene rubber, ethylene-propylene rubber, styrene-butadiene-styrene block copolymer or its hydrogenate, ethylene-propylene-diene terpolymer, styrene-ethylene-butadiene-ethylene copolymer, styrene-isoprene-styrene block copolymer, isotactic-1,2-polybutadiene, polyvinyl acetate, ethylene-vinyl acetate copolymer, propylene-α-olefin copolymer, polyvinylidene fluoride, polytetrafluoroethylene, fluorinated polyvinylidene fluoride, and polytetrafluoroethylene-ethylene copolymer.

[0102] In the secondary battery mentioned in the present application, a separator is usually provided between the positive electrode and the negative electrode to prevent short circuit. The material and shape of the separator are not particularly limited as long as the effect of the present application is not significantly impaired.

[0103] In one embodiment, the separator includes a porous sheet or non-woven fabric having excellent liquid retention. The materials of the resin or glass fiber separator include, but are not limited to, polyolefin, aromatic polyamide, polytetrafluoroethylene, polyethersulfone, and the like.

[0104] In one embodiment, the polyolefin is polyethylene or polypropylene.

[0105] In some embodiments, the polyolefin is polypropylene. The above-mentioned materials for the diaphragm can be used alone or in any combination.

[0106] In some embodiments, the secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.

[0107] In some embodiments, the outer packaging of the secondary battery may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0108] In some embodiments, the type of the electrolyte is not specifically limited. The electrolyte includes an electrolyte salt and an organic solvent. The specific types of the electrolyte salt and the organic solvent are not specifically limited and can be selected according to actual needs. The electrolyte may also include additives. The types of the additives are not particularly limited and may be film-forming additives for the positive electrode and / or the negative electrode, or additives that can improve certain properties of the battery, such as additives that improve the high or low temperature performance of the battery.

[0109] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square, or any other shape.

[0110] An embodiment of the present application provides an electric device, comprising the secondary battery described above, wherein the secondary battery serves as a power supply for the electric device.

[0111] Exemplarily, the above-mentioned electrical devices may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.

[0112] The present application is further described below with specific embodiments:

[0113] Example 1

[0114] A method for preparing a secondary battery comprises the following steps:

[0115] (1) Preparation of positive electrode sheet:

[0116] 1. A method for preparing a positive electrode material, comprising the following steps: first, 9.5 kg of iron phosphate, 2.8 kg of lithium hydroxide, 8.9 kg of lithium dihydrogen phosphate, 8.6 kg of manganese carbonate, and 0.11 kg of titanium dioxide are added to a battery powder mixer, and 30 L of pure water is used as a solution for mixing. At this time, the manganese-iron ratio is about 1.1. The initial solution pH value is adjusted to 8.2 using an ammonia complexing agent, and an ammonia complexing agent (concentration of 25%) is added during the initial 1 hour of stirring. The ammonia injection speed is regulated by a liquid flow meter to maintain at 5 L / H, and the pH value of the mixed solution is gradually increased to 10.2. Thus, the first half is a mixing and stirring process with a variable pH value (gradually rising from 8.2 to 10.2), and then the mixing and stirring is continued for 1 hour until the precipitation is complete. The precipitate in the solution was filtered out, and the precipitate was pre-sintered at 500°C for 2 h in a nitrogen protective atmosphere to obtain a precursor. The precursor was allowed to stand and return to room temperature before being finely ground, and then sintered at 700°C for 2 h. The positive electrode material was then crushed and sieved to remove iron.

[0117] 2. Preparation of positive electrode sheet: The prepared positive electrode material, acetylene black conductive agent, and polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 90:5:5, and N-methyl-2-pyrrolidone (NMP) is used as a solvent to obtain positive electrode slurry. The slurry is then coated on aluminum foil by extrusion coating, dried in an oven at 80°C, and then rolled by a roller press to obtain a positive electrode sheet.

[0118] (2) Preparation of negative electrode sheet: Graphite is selected as the negative electrode active material, mixed with acetylene black conductive agent, CSM / SBR in a mass ratio of 90:5:5, and water is used as the solvent to obtain negative electrode slurry after mixing. The slurry is coated on copper foil by extrusion coating, dried in an oven at 80°C, and then rolled by a roller press to obtain a negative electrode sheet.

[0119] (3) Isolation membrane: 20 μm PP / PE composite membrane with 10 μm PVDF modified coating on the surface.

[0120] (4) Preparation of electrolyte: Ethylene carbonate and diethyl carbonate were mixed in a ratio of 1:1, and then 1 M LiPF 6 The solution is stirred and mixed to be used as the electrolyte of lithium-ion battery. (5) Preparation of secondary battery:

[0121] The positive electrode sheet, negative electrode sheet and isolation film prepared above are wound in a predetermined order to prepare a bare cell, and the bare cell is placed in an outer packaging aluminum-plastic film, baked to remove moisture, injected with electrolyte, and vacuum packaged to prepare a secondary battery.

[0122] Examples 2 to 5, Comparative Example 2

[0123] The difference between Examples 2 to 5 and Comparative Example 2 and Example 1 is that the preparation methods of the positive electrode materials are different. Examples 2 to 5 change the variance of the manganese-iron ratio by changing the pH value variation law.

[0124] Example 2

[0125] The entire preparation process is consistent with Example 1 except that the change rule of pH is adjusted by adding ammonia water. The specific process is to adjust the initial solution pH value to 9.5 using ammonia water complexing agent, and add ammonia water (concentration of 25%) complexing agent during the initial 1h stirring process, and use a liquid flow meter to control the ammonia water injection speed to maintain at 2L / H, so that the pH value of the mixed solution is gradually increased to 10.2. Thus, the first half is a mixing and stirring process of changing pH value (gradually rising from 9.5 to 10.2), and then the mixing and stirring is continued for 1h until the precipitation is complete.

[0126] Example 3

[0127] The entire preparation process is consistent with Example 1 except that the change rule of pH is adjusted by adding ammonia water. The specific process is to adjust the initial solution pH value to 8.5 using ammonia water complexing agent, and add ammonia water (concentration of 25%) complexing agent during the initial 1h stirring process, and use a liquid flow meter to control the ammonia water injection speed to maintain at 4L / H, so that the pH value of the mixed solution is gradually increased to 10.2. Thus, the first half is a mixing and stirring process of changing pH value (gradually rising from 8.5 to 10.2), and then the mixing and stirring is continued for 1h until the precipitation is complete.

[0128] Example 4

[0129] The entire preparation process is the same as that in Example 1 except that the change rule of pH is adjusted by adding ammonia water. The specific process is that the initial solution pH value is adjusted to 8 by using ammonia water complexing agent, and ammonia water (concentration is 25%) complexing agent is added during the 2h stirring process, and the ammonia water injection speed is regulated by a liquid flow meter to maintain at 2L / H, and the pH value of the mixed solution is gradually increased to 10.2. Thus, the entire stirring process is a mixed stirring process with a variable pH value (gradually rising from 8 to 10.2) until the precipitation is complete.

[0130] Example 5

[0131] The entire preparation process is the same as that in Example 1 except that the change rule of pH is adjusted by adding ammonia water. The specific process is that the initial solution pH value is adjusted to 8 by using ammonia water complexing agent, and ammonia water (concentration is 25%) complexing agent is added during the 4h stirring process, and the ammonia water injection speed is regulated by a liquid flow meter to maintain at 1L / H, and the pH value of the mixed solution is gradually increased to 10.2. Thus, the entire stirring process is a mixed stirring process with a variable pH value (slowly rising from 8 to 10.2) until the precipitation is complete.

[0132] Comparative Example 2

[0133] Except for changing the ratio of the initial iron source to the manganese source, the rest of the preparation process is consistent with Example 1. The specific change is to add 12Kg of iron phosphate, 2.8Kg of lithium hydroxide, 8.9Kg of lithium dihydrogen phosphate, 3.7Kg of manganese carbonate, and 0.11kg of titanium dioxide to the battery powder mixer, and mix them with 30L of pure water as a solution. At this time, the manganese-iron ratio is about 0.4.

[0134] Embodiments 6 to 9

[0135] The difference between Examples 6 to 9 and Example 1 is that the preparation methods of the positive electrode materials are different. Examples 6 to 9 change the amount of manganese source and iron source added, thereby changing the expected value of the manganese-iron element ratio.

[0136] Example 6

[0137] Except for changing the ratio of the initial iron source to the manganese source, the rest of the preparation process is consistent with Example 1. The specific change is to add 11Kg of iron phosphate, 2.8Kg of lithium hydroxide, 8.9Kg of lithium dihydrogen phosphate, 7.5Kg of manganese carbonate, and 0.11kg of titanium dioxide to the battery powder mixer, and mix them with 30L of pure water as a solution. At this time, the manganese-iron ratio is about 0.9.

[0138] Example 7

[0139] Except for changing the ratio of the initial iron source to the manganese source, the rest of the preparation process is consistent with Example 1. The specific change is to add 9.2Kg of iron phosphate, 2.8Kg of lithium hydroxide, 9.2Kg of lithium dihydrogen phosphate, 8.8Kg of manganese carbonate, and 0.11kg of titanium dioxide to the battery powder mixer, and mix them with 30L of pure water as a solution. At this time, the manganese-iron ratio is about 1.3.

[0140] Example 8

[0141] Except for changing the ratio of the initial iron source to the manganese source, the rest of the preparation process is consistent with Example 1. The specific change is to add 8.3Kg of iron phosphate, 2.8Kg of lithium hydroxide, 9.6Kg of lithium dihydrogen phosphate, 9.5Kg of manganese carbonate, and 0.11kg of titanium dioxide to the battery powder mixer, and mix them with 30L of pure water as a solution. At this time, the manganese-iron ratio is about 1.5.

[0142] Example 9

[0143] Except for changing the ratio of the initial iron source to the manganese source, the rest of the preparation process is consistent with Example 1. The specific change is to add 7Kg of iron phosphate, 2.8Kg of lithium hydroxide, 8.9Kg of lithium dihydrogen phosphate, 11Kg of manganese carbonate, and 0.11kg of titanium dioxide to the battery powder mixer, and mix them with 30L of pure water as a solution. At this time, the manganese-iron ratio is about 2.

[0144] Embodiments 10 to 15

[0145] The difference between Examples 10 to 15 and Example 1 is that the preparation method of the positive electrode material is different. Examples 10 to 15 change the position of the first peak and the second peak as well as S1 and S2 by changing the temperature and time during the sintering process and the crushing and screening steps.

[0146] Example 10

[0147] The entire preparation process is the same as that in Example 1 except that the temperature and time during the sintering process are changed. The precipitate in the solution is filtered out, and the precipitate is pre-sintered at 500°C for 2.25h in a nitrogen atmosphere to obtain a precursor, which is then finely ground after being allowed to stand and return to room temperature, and then sintered at 700°C for 2h, and then crushed and sieved to remove iron to obtain the positive electrode material.

[0148] Embodiment 11

[0149] The entire preparation process is the same as that in Example 1 except that the temperature and time during the sintering process are changed. The precipitate in the solution is filtered out, and the precipitate is pre-sintered at 500°C for 1.75h in a nitrogen atmosphere to obtain a precursor, which is then finely ground after being allowed to stand and return to room temperature, and then sintered at 700°C for 2h, and then crushed and sieved to remove iron to obtain the positive electrode material.

[0150] Example 12

[0151] The entire preparation process is the same as that in Example 1 except that the temperature and time during the sintering process are changed. The precipitate in the solution is filtered out, and the precipitate is pre-sintered at 500°C for 3 h in a nitrogen atmosphere to obtain a precursor, which is then finely ground after being allowed to stand and return to room temperature, and then sintered at 700°C for 1 h, and then crushed and sieved to remove iron to obtain the positive electrode material.

[0152] Example 13

[0153] The entire preparation process is the same as that in Example 1 except that the temperature and time during the sintering process are changed. The precipitate in the solution is filtered out, and the precipitate is pre-sintered at 400°C for 2 h in a nitrogen atmosphere to obtain a precursor, which is then finely ground after being allowed to stand and return to room temperature, and then sintered at 600°C for 2 h, and then crushed and sieved to remove iron to obtain the positive electrode material.

[0154] Embodiment 14

[0155] The entire preparation process is the same as that in Example 1 except that the temperature and time during the sintering process are changed. The precipitate in the solution is filtered out, and the precipitate is pre-sintered at 500°C for 2.25h in a nitrogen atmosphere to obtain a precursor, which is then finely ground after being allowed to stand and return to room temperature, and then sintered at 800°C for 2h, and then crushed and sieved to remove iron to obtain the positive electrode material.

[0156] Embodiment 15

[0157] The entire preparation process is the same as that in Example 1 except that the temperature and time during the sintering process are changed. The precipitate in the solution is filtered out, and the precipitate is pre-sintered at 600°C for 2.25h in a nitrogen atmosphere to obtain a precursor, which is then finely ground after being allowed to stand and return to room temperature, and then sintered at 900°C for 2h, and then crushed and sieved to remove iron to obtain the positive electrode material.

[0158] Embodiments 16 to 19

[0159] The difference between Examples 16 to 19 and Example 1 is that, based on Example 1, Examples 16 to 19 form a carbon coating layer on the surface of the positive electrode material.

[0160] The specific method is: the positive electrode material of Example 1 is mixed evenly with anhydrous glucose in water, filtered, dried, and then sintered to coat the carbon material on the surface of the positive electrode material.

[0161] The coating layer shown in Table 1 was obtained by controlling the amount of anhydrous glucose added and the sintering parameters.

[0162] Example 16

[0163] 10 kg of the positive electrode powder material obtained in Example 1, 0.1 kg of anhydrous glucose, and 70 kg of pure water were mixed in a sand mill, and the powder was calcined at 700° C. for 9 h in a nitrogen atmosphere, and then crushed and screened to obtain a positive electrode material with a surface carbon coating.

[0164] Embodiment 17

[0165] 10 kg of the positive electrode powder material obtained in Example 1, 0.2 kg of anhydrous glucose, and 70 kg of pure water were mixed in a sand mill, and the powder was calcined at 700° C. for 9 h in a nitrogen atmosphere, and then crushed and screened to obtain a positive electrode material with a surface carbon coating.

[0166] Embodiment 18

[0167] 10 kg of the positive electrode powder material obtained in Example 1, 1.4 kg of anhydrous glucose, and 70 kg of pure water were mixed in a sand mill, and the powder was calcined at 700° C. in a nitrogen atmosphere for 9 h. After being crushed and screened, a positive electrode material with a surface carbon coating was obtained.

[0168] Embodiment 19

[0169] 10 kg of the positive electrode powder material obtained in Example 1, 1.8 kg of anhydrous glucose, and 70 kg of pure water were mixed in a sand mill, and the powder was calcined at 700° C. for 9 h in a nitrogen atmosphere, and then crushed and screened to obtain a positive electrode material with a surface carbon coating.

[0170] Comparative Example 1

[0171] A method for preparing a positive electrode material comprises the following steps:

[0172] 9.67 kg of ferric nitrate, 10.74 kg of manganese nitrate and 19.21 kg of citric acid were dissolved in pure water, and the pH value of the mixed solution was adjusted to 10.5. The mixture was sealed, heated and stirred at 70°C for 12 hours. The above powder was calcined at 250°C for 2 hours, cooled and ground, and then the powder was calcined at 450°C in a nitrogen atmosphere for 2 hours. After grinding, all the powder, 7.61 kg of lithium carbonate, 11.50 kg of diammonium phosphate, 1.34 kg of sucrose and 70 kg of pure water were mixed evenly and sand-milled. The powder was calcined at 700°C in a nitrogen atmosphere for 9 hours, and then crushed and sieved to obtain the positive electrode material.

[0173] Test Example 1

[0174] The positive electrode materials of the embodiment and the comparative example were tested by laser diffraction method to obtain particle size distribution curves. The specific positions of the diffraction peaks are shown in Table 1.

[0175] Among them, the particle size distribution curves of Example 1 and Comparative Example 1 are as follows: Figure 1 As shown, from Figure 1 It can be seen that the positive electrode material described in this application (non-uniform distribution in the figure) has a wider particle size distribution range and presents two typical particle size distribution ranges (200-270nm, 360-470nm), while the particle size distribution range of Comparative Example 1 (uniform distribution in the figure) is relatively concentrated (240-420nm). This result shows that we have successfully prepared positive electrode materials with similar average particle sizes but very different particle size distribution trends.

[0176] Test Example 2

[0177] The abscissa of the manganese-iron element distribution intensity curve of the positive electrode material of the embodiment and the comparative example is divided into 16 parts, and the manganese-iron element ratio corresponding to the abscissa of each divided point is calculated. The manganese-iron element ratio normal distribution curve is constructed for the values ​​of the manganese-iron element ratio of the 16 points, thereby obtaining μ (expected value) and σ 2 Value (variance).

[0178] The distribution diagrams and variances of ferromanganese elements and the ferromanganese element ratios of Example 1 and Comparative Example 1 are shown in Table 1. Figure 2 , Figure 3 As shown in Figure 2, in addition to the non-uniform distribution of particle size, the non-uniform distribution of manganese and iron atoms inside the particles was also verified by transmission electron microscopy combined with image recognition methods. Figure 2As shown in the figure, by microscopically characterizing the prepared lithium manganese iron phosphate particles, the corresponding Mn / Fe element distribution mapping diagram can be obtained. Combined with image processing methods, the Mn / Fe element ratio in different regions inside the particles can be quantitatively analyzed. The obtained Mn / Fe element distribution mapping diagram is approximately divided into 16 equal parts to obtain the Mn / Fe ratio value Xn (n = 1, 2...16) in each sample. By arranging the statistical data of the 16 Mn / Fe ratios, a normal distribution curve X~N (μ, σ 2 ).like Figure 2 As shown in the figure, the statistical results of the samples with uneven element distribution inside the particles found that the mean Mn / Fe ratio was 1.171, with a variance of σ 2 =0.118, the overall ratio range covers 0.9-1.41, which is relatively dispersed. Figure 3 The elements in the particles are evenly distributed. The statistical results show that the mean Mn / Fe ratio is 1.186, with a variance of σ 2 =0.038, the overall ratio ranges from 1.12 to 1.28, and the distribution range is concentrated.

[0179] Table 1 Parameters

[0180]

[0181] Performance Testing

[0182] 1. Cycle test:

[0183] a. Place the secondary battery in a 25℃ test cabinet and let it sit for half an hour until the temperature is uniform;

[0184] b. Charge at 0.33C rate to 4.35V and then keep constant voltage until the current decreases to 0.05C rate;

[0185] c. Let it sit for half an hour.

[0186] d. Discharge at a rate of 0.33C to 2.5V, and read the discharge capacity Cn (n=1, 2, 3, ...).

[0187] e. Let stand for half an hour;

[0188] f. Cycle test steps bd process 400 cycles, calculate the ratio of each cycle discharge capacity Cn to the first cycle discharge capacity C1, and obtain the cycle capacity retention rate.

[0189] 2.DCR internal resistance test

[0190] a. Charge at a rate of 0.33C to 4.35V and then maintain constant voltage until the current decreases to a rate of 0.05C.

[0191] b. Let it sit for half an hour.

[0192] c. 0.33C rate current discharge for 90 min (50% SOC).

[0193] d. Let stand for half an hour.

[0194] e. Discharge at 3C rate for 30s, record the current and voltage during the discharge process, read the voltage before discharge V1, the voltage after 30s of discharge V2, and the discharge current A0, and the corresponding test DCR = V1-V2 / A0.

[0195] Table 2 Performance test results

[0196]

[0197]

[0198] It can be seen from Table 2 that the positive electrode material described in the present application can significantly improve the cycle life of the secondary battery and reduce the DCR.

[0199] By comparing Example 1 with Comparative Examples 1 to 2, it can be seen that the present invention controls: 0.5≤μ, σ 2 ≥0.05; significantly improves the cycle life of the secondary battery and reduces DCR.

[0200] Comparing Examples 1 to 5, it can be seen that the present invention controls 0.1≤σ 2 ≤0.15, further improving the cycle life of the secondary battery and reducing the DCR.

[0201] By comparing Examples 1 and 6 to 9, it can be seen that the present application further improves the cycle life of the secondary battery and reduces the DCR by controlling: 1.17≤μ≤1.5.

[0202] By comparing Examples 1 and 10 to 12, it can be seen that the present application further improves the cycle life of the secondary battery and reduces the DCR by controlling 1.2≤S1 / S2≤1.5.

[0203] By comparing Examples 1 and 13 to 15, it can be seen that the present application further improves the cycle life of the secondary battery and reduces the DCR by controlling the first peak on the particle size distribution curve of the positive electrode material to be between 240 and 270 nm and the second peak to be between 420 and 440 nm.

[0204] By comparing Examples 1 and 16 to 19, it can be seen that the present application further improves the cycle life of the secondary battery and reduces the DCR by coating the coating layer on the surface of the positive electrode material.

[0205] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present application rather than to limit the scope of protection of the present application. Although the present application has been described in detail with reference to the preferred embodiments, ordinary technicians in this field should understand that the technical solution of the present application can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present application.

Claims

1. A positive electrode material, characterized in that: including lithium iron manganese oxide; The positive electrode material satisfies: 0.5≤μ, σ 2 ≥0.05; Wherein, μ is the expected value of the normal distribution curve of the manganese-iron element ratio in the positive electrode material; σ 2 is the variance of the normal distribution curve of the manganese-iron element ratio in the positive electrode material.

2. The positive electrode material according to claim 1, characterized in that The average manganese to iron ratio of the positive electrode material is 0.25-4.

3. The positive electrode material according to claim 1, characterized in that The particle size distribution curve of the positive electrode material includes a first peak and a second peak; the first peak is located between 100 and 300 nm, and the second peak is located between 300 and 800 nm.

4. The positive electrode material according to claim 1, characterized in that The peak area of ​​the first peak is S1, and the peak area of ​​the second peak is S2, satisfying: 1≤S1 / S2≤4.

5. The positive electrode material according to claim 4, characterized in that 0.5≤S1 / (S1+S2)≤0.8; and / or 0.2≤S2 / (S1+S2)≤0.

5.

6. The positive electrode material according to claim 1, characterized in that It also includes a coating layer arranged on the outer surface of the manganese iron lithium oxide, and the coating layer includes at least one of a carbon-based material, a metal oxide, and an ion conductor.

7. The positive electrode material according to claim 6, characterized in that Satisfy at least one of the following (1) to (5): (1) The carbon-based material includes one or more of artificial graphite, natural graphite, soft carbon, and hard carbon; (2) The metal oxide includes at least one of aluminum oxide, magnesium oxide, titanium dioxide, lanthanum oxide, zirconium dioxide, antimony trioxide, antimony pentoxide, vanadium trioxide, vanadium pentoxide, and zinc oxide; (3) The ion conductor includes at least one of LLZO, LLTO, LATP, sulfide solid electrolyte, and polymer ion conductor; (4) The thickness of the coating layer is 1 to 100 nm; (5) The coating layer accounts for 0.5 to 5% of the total mass of the positive electrode material.

8. The positive electrode material according to claim 1, characterized in that The manganese iron lithium oxide includes a compound with the molecular formula Li x Mn y Fe 1-y M z PO4, where 0.9 ≤ x ≤ 1.1, 0 < y < 1, 0 ≤ z ≤ 0.05, and M includes at least one of In, La, Zr, Ce, W, Al, Ti, Sr, Mg, Sb, V, Zn, Cu, and Cr.

9. A secondary battery, characterized in that: It comprises a positive electrode plate, wherein the positive electrode plate comprises the positive electrode material according to any one of claims 1 to 8.

10. An electrical device, characterized in that: A secondary battery comprising the secondary battery according to claim 9.